LUDICITY AS A POSSIBILITY OF EDUCATIONAL STRATEGY IN THE LEARNING PROCESS IN THE EARLY YEARS OF ELEMENTARY EDUCATION I - Barbosa Nery, Bernadeth (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to show that conflicts of coexistence, interaction and sociability were very accentuated with the return to face-to-face classes in the physical space of the school after the most serious period of the pandemic in 2022. Linked to this situation, teachers observed an increase of the learning deficit during the period that students were taking classes at home via remote learning. This topic is burning nowadays. Thus, the general objective of the work is to show how playfulness can mobilize educational well-being strategies to reduce coexistence conflicts and enhance learning processes in relation to the return to face-to-face classes at school in pandemic times among students in the initial years of Fundamental Teaching I. The methodology used uses the bilbiographical method and qualitative approach (MINAYO, 2001) using publications, informational and communicative reports and articles from the internet that debate school conflicts in the return to face-to-face classes after the most critical period of the pandemic . The reflection and debate resulting from the study proposes pedagogical strategies based on playfulness to combine with other strategies the reconstruction of new educational horizons that help in the development of educational innovation in contemporary times. Therefore, a brief contextualization of the events is necessary to demonstrate a little of the scenario in times of a pandemic, specifically, school conflicts most debated by teachers in internet publications, the school phase chosen is the initial years of Elementary School I. In In short, develop other ways of inserting playfulness and we propose play structures within this new educational process.